Evaluation of immune sensor responses to a viral small noncoding RNA - Kara, Mehmet; Tibbetts, Scott A. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionGammaherpesviruses are widespread pathogens causing persistent infections linked to the development of numerous types of lymphomas in humans. During latency, most of the viral protein-coding genes are suppressed, facilitating evasion of adaptive immune recognition of protein antigens. In contrast, many noncoding RNA (ncRNA) molecules are expressed in infected cells and can regulate key cellular pathways while simultaneously evading adaptive immune recognition. To counteract this, many cells express internal pattern recognition receptors that can intrinsically sense ongoing infections and initiate cellular defenses. Murine gammaherpesvirus 68 (MHV68) is a valuable model to study in vivo aspects of gammaherpesvirus pathogenesis. The MHV68 ncRNA TMER4 (tRNA-miRNA-encoding RNA 4) promotes lymph node egress of infected B cells: in the absence of TMER4, MHV68-infected B cells accumulate in the lymph node in a manner similar to B cells activated through specific antigen encounter.MethodWe hypothesized that TMER4 may alter intrinsic immune activation. In research described here, we aimed to explore the immunomodulatory functions of TMER4 by evaluating its impact on signaling through the critical immune sensors Toll-like receptor 4 (TLR4), TLR3, TLR7, and retinoic acid-inducible gene I (RIG-I). To accomplish this, we developed a system to test noncoding RNAs using commercially available reporter cell lines. We optimized the experimental procedure to ensure ncRNA expression and to quantify immune sensory molecule induction or inhibition by the expressed ncRNA.Results and discussionExpression of TMER4 RNAs from plasmid constructs did not alter TLR or RIG-I signaling. This study provides a clear experimental framework that can be applied to test other small ncRNAs for their impact on various innate immune sensor proteins.